2018
DOI: 10.17559/tv-20160927163837
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Fuzzy Analytic Hierarchy Process in Urban Mobility System

Abstract: Importance of urban mobility system is increasing from year to year. This is the reason why decision making process is increasingly complex requiring taking into account more and more different criteria. One of the important and commonly used techniques that support decision making processes is Analytic Hierarchy Process (AHP) while for the purpose of supporting a more realistic way of decision making, fuzzy logic is used. The paper examines the use of fuzzy analytical hierarchy process (FAHP) in the urban mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In order to rationalize the uncertainty accompanying the decision-making process, it is necessary that new approaches to dealing with uncertainty within the conventional AHP process, such as fuzzy Set Theory, should be incorporated. Fuzzy logic provides a more realistic way for dealing with undetermined human judgments [21], this theory is oriented towards the conversion of human perceptions, such as linguistic statements, into an arithmetical form by representing vague data by using fuzzy numbers [22]. Triangular fuzzy Numbers (TFN) are most often used to describe fuzzy events.…”
Section: The Fuzzy Ahp Methodsmentioning
confidence: 99%
“…In order to rationalize the uncertainty accompanying the decision-making process, it is necessary that new approaches to dealing with uncertainty within the conventional AHP process, such as fuzzy Set Theory, should be incorporated. Fuzzy logic provides a more realistic way for dealing with undetermined human judgments [21], this theory is oriented towards the conversion of human perceptions, such as linguistic statements, into an arithmetical form by representing vague data by using fuzzy numbers [22]. Triangular fuzzy Numbers (TFN) are most often used to describe fuzzy events.…”
Section: The Fuzzy Ahp Methodsmentioning
confidence: 99%
“…Furthermore, in the review conducted by Kramar and Topolšek [25], which focused on applying the Fuzzy Analytic Hierarchy Process (F-AHP) method in the urban mobility field, there is only one reference linked to freight logistics. This same paper has also been identified in the current literature review.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…A detailed review of Fuzzy logic and AHP and some of their applications can be found in the following citations: (Baumann et al, 2019;Guersola et al, 2018;Kaymaz et al, 2021;Kramar & Topolšek, 2018;Liu et al, 2020;Navarro et al, 2020;Pelissari et al, 2021;Ruiz Bargueño et al, 2021;Sarjono et al, 2020;Sitorus et al, 2019;Yap et al, 2019).…”
Section: Fuzzy Logic and Ahpmentioning
confidence: 99%